Development of a character recognition software to solve a Sudoku puzzle - Dutta, Akash; Ghosh, Arunabha (2016 IEEE 7th Annual Information Technology, Electronics and Mobile Communication Conference (IEMCON), 2016)
An Image is a visual representation of any object, place, person etc. In the field of Computer Science a Digital Image is a numeric representation of a two-dimensional image. Often images may contain texts, which are a sequence of human-readable characters. Our general conundrum is extraction of texts from an image for processing and editing. In an image texts are defined by set of pixels just like any other object and thus cannot be processed or edited. In this work we have strived to develop a system which can extract texts from a digital image of a Sudoku puzzle, solve the puzzle, and then provide a solution. Our approach is specific but its application are varied.